Tracked Changes. Electric cables. Calculation of the current rating. Current rating equations (100 % load factor) and calculation of losses. Current sharing between parallel single-core cables and calculation of circulating current losses Part 1-3, (23rd June 2023) - British Standards Institution,
No abstract available